Building Institutions in Post-conflict African Economies. - Aron, J (Wiley, 2003)
Institutions are altered by conflict, depending on the scale, duration and type of conflict. At one extreme, formal political, social and economic institutions may be completely destroyed (e.g. Somalia), while the importance and type of informal institutions may be changed. This survey addresses some of the current issues in the design and implementation of institution-building and reform in sub-Saharan Africa, and highlights the particular difficulties faced by post-conflict countries. However, research on practical policy interventions toward institution-building is still at an early stage.